Hepatic growth hormone - JAK2 - STAT5 signalling: Metabolic function, non-alcoholic fatty liver disease and hepatocellular carcinoma progression. (December 2019) - Kaltenecker, Doris; Themanns, Madeleine; Mueller, Kristina M.; Spirk, Katrin; Suske, Tobias; Merkel, Olaf; Kenner, Lukas; Luís, Andreia; Kozlov, Andrey; Haybaeck, Johannes; Müller, Mathias; Han, Xiaonan; et al.
Highlights: Disruption of GH-JAK2-STAT5 signalling induces hepatic steatosis. Hepatic STAT5 executes tumour suppressive functions in HCC development. Hepatic JAK2 exerts oncogenic functions in HCC development. Divergent role of GH signalling in oxidative stress and damage management. Abstract: The rising prevalence of obesity came along with an increase in associated metabolic disorders in Western countries. Non-alcoholic fatty liver disease (NAFLD) represents the hepatic manifestation of the metabolic syndrome and is linked to primary stages of liver cancer development. Growth hormone (GH) regulates various vital processes such as energy supply and cellular regeneration. In addition, GH regulates various aspects of liver physiology through activating the Janus kinase (JAK) 2- signal transducer and activator of transcription (STAT) 5 pathway. Consequently, disrupted GH - JAK2 - STAT5 signaling in the liver alters hepatic lipid metabolism and is associated with NAFLD development in humans and mouse models. Interestingly, while STAT5 as well as JAK2 deficiency correlates with hepatic lipid accumulation, recent studies suggest that these proteins have unique ambivalent functions in chronic liver disease progression and tumorigenesis. In this review, we focus on the consequences of altered GH - JAK2 - STAT5 signaling for hepatic lipid metabolism and liver cancer development with an emphasis on lessons learned from genetic knockout models.